2015
DOI: 10.1016/j.jpowsour.2015.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional phase field based finite element study on Li intercalation-induced stress in polycrystalline LiCoO2

Abstract: In this study, the stress generation of LiCoO2 with realistic 3D microstructures has been studied systematically. Phase field method was employed to generate the 3D microstructures with different grain sizes. The effects of grain size, grain crystallographic orientation, and grain boundary diffusivity on chemical diffusion coefficient and stress generation were studied using finite element method. The calculated chemical diffusion coefficient is about in the range of 8.5×10 -10 cm 2 /s to 3.6×10 -9 cm 2 /s. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…It is shown that the ideal solution thermodynamics assumption was applied in describing the transport of lithium ions and diffusion induced stress, and is widely used in battery modeling [12][13][14][21][22][23]. Hence, the transport of Lithium ions in active particles is described by the modified Fick's law [12,24], which includes the effect of stress on diffusion:…”
Section: Electrochemistrymentioning
confidence: 99%
“…It is shown that the ideal solution thermodynamics assumption was applied in describing the transport of lithium ions and diffusion induced stress, and is widely used in battery modeling [12][13][14][21][22][23]. Hence, the transport of Lithium ions in active particles is described by the modified Fick's law [12,24], which includes the effect of stress on diffusion:…”
Section: Electrochemistrymentioning
confidence: 99%
“…One of the critical challenges of LIBs is to enhance the mechanical stability of electrode materials. Diffusion induced stresses [8,9] and phase transition [10,11] during the operations of LIBs can cause fracture and mechanical failure. Hence, it is important to understand the stress generation in battery materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been done to study the stress generation to prevent the mechanical failures of LIBs [9,[12][13][14][15][16]. Zhang et al [14,15] studied the diffusion induced stresses in LiMn2O4 under galvanostatic and potentiodynamic conditions using ellipsoid shaped particle model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model doesn't include the stress analysis caused by lithium intercalation. Our previous study [19] showed the effective Li diffusivity and stress generation are strongly affected by grain orientation, grain size and grain boundary diffusivity. In this study, the major contribution is to demonstrate the importance to include anisotropic property in the model.…”
Section: Introductionmentioning
confidence: 95%